Structural and biochemical characterization of Human PR70 in isolation and in complex with the scaffolding subunit of protein phosphatase 2A - Dovega, Rebecca (2014)
Protein Phosphatase 2A (PP2A) is a major Ser/Thr phosphatase involved in the regulation of various cellular processes. PP2A assembles into diverse trimeric holoenzymes, which consist of a scaffolding (A) subunit, a catalytic (C) subunit and various regulatory (B) subunits. Here we report a 2.0 Å crystal structure of the free B’’/PR70 subunit and a SAXS model of an A/PR70 complex. The crystal structure of B’’/PR70 reveals a two domain elongated structure with two Ca2+ binding EF-hands. Furthermore, we have characterized the interaction of both binding partner and their calcium dependency using biophysical techniques. Ca2+ biophysical studies with Circular Dichroism showed that the two EF-hands display different affinities to Ca2+. In the absence of the catalytic C-subunit, the scaffolding A-subunit remains highly mobile and flexible even in the presence of the B’’/PR70 subunit as judged by SAXS. Isothermal Titration Calorimetry studies and SAXS data support that PR70 and the A-subunit have high affinity to each other. This study provides additional knowledge about the structural basis for the function of B’’ containing holoenzymes.